Sport psychology: Psychologic issues and applications - Carr, C. M. (Physical Medicine & Rehabilitation Clinics of North America, 2006)
This article has briefly highlighted the area of sport psychology as it relates to performance psychology skills (mental training), including a historical overview and current topics overview. The use of mental training skills may be of interest to the practicing physical medicine and rehabilitation professional in the treatment of his or her patients. It is important that the physical medicine professional recognize what sport or performance psychology represents within the paradigm of psychologic interventions. Referring to an individual based on his or her training (licensed psychologist versus mental training consultant) is essential for the appropriate management of psychologic issues related to performance. The issues related to the psychologic rehabilitation of the injured athlete are of importance to the medical staff; the overview of affective responses can assist in understanding the normal and adaptive responses of the injured athlete. Finally, a brief description of a psychologist's role within a sports medicine and rehabilitation practice is presented. The psychologic issues that are present in the world of sport and elite performance are numerous, and not all are mentioned in this article. Issues of eating disorders, substance abuse, and psychologic health with athletes should be further explored within the physical medicine and rehabilitation discipline as well as in the sports medicine discipline. The ever-evolving psychologic dynamics of individuals involved in sport and elite performance are intriguing and unique. A specialized knowledge base, training, and experience in providing psychologic services are required to treat this unique population. Counseling and clinical issues of the athlete and elite performer require further attention in the realm of psychologic interventions, including further exploration of the efficacy of interventions for performance enhancement. The field of applied sport psychology may offer the physical medicine professional a unique perspective into the care of patients who are athletes and elite performers.